A new species of Lobelia (Campanulaceae: Lobelioideae) from the Sierra Madre Oriental, Mexico - Pérez-Pérez, Miguel A.; Ayers, Tina J.; Amith, Jonathan D. (Phytotaxa, 2022)
Lobelia alanae sp. nov. from Puebla and Veracruz, Mexico, is described from four known populations in tropical deciduous forests from 153 to 700 m elevation. This new species is compared to the closely related Lobelia porphyrea, a species known only from the type collection in the state of Hidalgo. Lobelia alanae can be separated from L. porphyrea by its height, hypanthium, calyx lobes and fruit. Based on the strongly reticulate-foveolate seed coats, L. alanae is hypothesized to be a new member of section Lobelia, previously comprising 22 species nearly endemic to the eastern U.S.